Effect of EMS and SA on Pollen sterility in Vigna radiata (L.) Wilczek (Mung bean) - Kulthe, Mukund P (Plantae Scientia, 2019)
The seeds of mung bean varieties were treated with the chemical mutagens viz EMS and SA to study pollen sterility. EMS with 0.05%, 0.10%, 0.15% concentrations and Sodium azide with 0.01%, 0.02%, 0.03% concentrations. Pollen sterility is directly proportional to concentrations ie. increase in concentrations increases pollen sterility.